Indian Vehicle Ownership: Insights from Literature Review, Expert Interviews, and State-Level Model - Bansal,P; Kockelman,KM (Journal of the Transportation Research Forum, 2017)
This study reviews existing vehicle ownership models for India and describes the results of nine experts’ interviews to gather insights about Indians’ travel patterns and vehicle choices. According to the experts, vehicle price, fuel economy, and brand (in declining importance) are the most decisive factors in Indians’ car purchase choices. This study also estimated household vehicle ownership levels across India’s 35 states using Census 2011 data. The results suggest that states with a higher proportion of computer-owning households and higher share of households living in rural areas with larger household size, ceteris paribus, are likely to have higher car ownership.